Pendampingan Pembuatan Legalitas Usaha dan Inovasi Kemasan dalam Upaya Peningkatan Penjualan Bakso Sapi Frozen - Kosim, Muhammad; Denny Saputera; Ilham Muhammad Mardiputra; Adi Maryadi; Fitri Amalia (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
This community service activity was carried out with the aim of increasing sales of Omasan Taste frozen beef meatballs through assistance in the business licensing process and updates in product packaging design. Small businesses like Omasan Taste often experience difficulties in obtaining official licenses and creating attractive and safe packaging. Through training, consultation, and assessment, this mentoring aims to assist in the setup and management of business licenses, such as P-IRT licensing and halal certification, as well as improved packaging design. The results showed that having a complete business license can increase customer confidence, while attractive and informative packaging design succeeded in increasing interest in the product. This is reflected in increased purchases and market expansion. In this way, the assistance successfully boosted Omasan Taste's sales through strategies to increase consumer confidence and product competitiveness in a larger market.